Perception of the culture and education programme of the Youth Olympic Games by the participating athletes: A case study for Innsbruck 2012 - Schnitzer, M.; Peters, M.; Scheiber, S.; Pocecco, E. (International Journal of the History of Sport, 2014)
The Youth Olympic Games (YOG) were introduced and officially inaugurated in Singapore in 2010, constituting the first new Olympic event to be staged since the 1924 Winter Olympic Games. The structure of the YOG is based on the model of the European Youth Olympic Festival, which was introduced three decades ago. Being a new international sports event targeting young athletes, a major innovation of the YOG is its unique Culture and Education Programme (CEP). To date, very little literature deals with the CEP and its influence on the athletes' overall experience. Thus, the objective of this study was to give a deeper insight into the athletes' perception of the CEP. A survey of 662 participating athletes as well as 6 focus groups with 43 athletes was conducted during the first 2012 Winter Youth Olympic Games in Innsbruck, Austria. The results of the focus groups corroborated the results of the survey: young athletes participating in the CEP liked it very much; nevertheless, the tight training and competition schedule represented an issue for many athletes. The findings of this study underline the necessity to plan the CEP more carefully and to raise interest in the CEP among coaches and Chefs de Mission.